Tubercular splenic abscess: Two case reports with review of literature - Subhra Mitra; Mrinmoy Mitra; Satyajeet Sahoo; Bijan Kumar Ghosh (The Journal of Association of Chest Physicians, 2015)
Tubercular splenic abscess is an extremely rare entity among immunocompetent individuals. Here we describe two cases of tubercular splenic abscess in immunocompetent individuals, the first had to undergo emergency splenectomy for pain abdomen. The second case presented with pyrexia of unknown origin where pus aspirated from spleen stained positive for acid fast bacilli. Both had favorable response to anti-tubercular therapy. Tuberculosis although uncommon should be kept as a differential diagnosis of splenic abscess presenting with pain abdomen or pyrexia of unknown origin with multiple hypodense lesions in spleen on imaging.